2018
DOI: 10.1590/s1980-220x2017011203306
|View full text |Cite
|
Sign up to set email alerts
|

Precisión y exhaustividad del registro de eventos adversos mediante una terminología de interfase

Abstract: Objective:To determine what adverse events, including pressure ulcers, infection of the surgical site and aspiration pneumonia, nurses record in clinical histories, in terms of diagnostic accuracy and completeness, through ATIC. Method: Observational, descriptive, cross-sectional, multicenter study of 64 medical-surgical and semi-critical units of two university hospitals in Catalonia, Spain, during 2015. The diagnostic accuracy was assessed by means of the correspondence between the event declared in the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
3
0
3
Order By: Relevance
“…Around 2% of patients experienced an AE, a frequency similar to those recorded in previous reports [7,11,[26][27][28][29]. In addition, 2.2% of patients died during hospitalization, again in line with other studies reporting rates ranging between 1-5% [9,30,31].…”
Section: Discussionsupporting
confidence: 88%
“…Around 2% of patients experienced an AE, a frequency similar to those recorded in previous reports [7,11,[26][27][28][29]. In addition, 2.2% of patients died during hospitalization, again in line with other studies reporting rates ranging between 1-5% [9,30,31].…”
Section: Discussionsupporting
confidence: 88%
“…The importance of the documentation supports the guaranteed continuity of safety policies, supported by electronic records and qualification and evaluation systems. 13 As for the third category, corresponding to strategies for successfully reporting the adverse event, in our study, we found several answers that point towards permanent education on the safety culture, effective and continuing communication with peers and heads, thus preserving confidence for the professional committing the error to report immediately, with the security that (s) he will not be punished.…”
Section: /10mentioning
confidence: 77%
“…Two of the hospitals participating in the study organise clinical care sessions, with the purpose of discussing a patient's SCP individualisation. The study conducted by González-Samartino et al (2018) shows that the nurses who participate in these sessions record adverse events in the individualised care plan with greater diagnostic accuracy and completeness. It would be desirable if hospitals found a way to enable nurses to attend these sessions, during the working hours of each shift, with the reassurance of knowing that the patients are receiving the appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some nurses still prefer to use progress notes to record the patient status. The conviction that they will be consulted by other professionals prior to looking at an individualised care plan and the habit of writing descriptions in free text (González-Samartino et al, 2018) means that their use prevails over individualised care plans.…”
Section: Discussionmentioning
confidence: 99%